Applied research in ecology and social sciences in support of sustainable management of forest ecosystems in Central Africa - CIFOR-ICRAF (CIFOR-ICRAF, 2022)
Over the next four years (2022–2025), the Center for International Forestry Research (CIFOR) and the International Center for Research in Agroforestry (ICRAF) will implement a support programme for applied research in ecology and social sciences. Its goal is to strengthen the impact of this research on the sustainable management of forest ecosystems in Central Africa.